2016
DOI: 10.14400/jdc.2016.14.5.149
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the influence of external knowledge network on SMEs' new technology development and technology commercialization capabilities in the perspective of open innovation

Abstract: In today's rapidly-changing business context with technology convergence among various fields, new technology development and technology commercialization capabilities are very important to the survival and growth of small and medium-sized enterprises (SMEs). This study develops the research model based on the open innovation perspective and empirically tests it by using 2,000 data from SMEs in South Korea. The empirical analysis result reveals that SMEs' external technology collaboration network and external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Moreover, the moderating role of environmental dynamism on the innovation-performance link was also assessed. (Hau, 2016;Kylä heiko et al, 2011) and somewhat similar to the outcome of the study of Lyver and Lu(2018), as they empirically confirmed that technological capabilities enhance the innovation practices (as one of the dimensions of strategic entrepreneurship) in SMEs.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the moderating role of environmental dynamism on the innovation-performance link was also assessed. (Hau, 2016;Kylä heiko et al, 2011) and somewhat similar to the outcome of the study of Lyver and Lu(2018), as they empirically confirmed that technological capabilities enhance the innovation practices (as one of the dimensions of strategic entrepreneurship) in SMEs.…”
Section: Discussionsupporting
confidence: 58%
“…In particular, small and medium enterprises (SMEs), which generally do not have sufficient internal capabilities and resources for innovation, can obtain external knowledge and experience that are essential for technology innovation through open innovation [39,40]. Hau [41] investigated the relationship between open innovation and the technology commercialization capability of SMEs. According to this research, SMEs' external technology collaboration network and external information network diversities have positive effects on their technology commercialization capability.…”
Section: Technology Commercialization Process and Open Innovationmentioning
confidence: 99%
“…Targeted Innovation Performance [26] External technology collaboration network diversity positively influences SMEs' technology management capabilities.…”
Section: References Major Finding Related To This Researchmentioning
confidence: 99%